A Bright, Nontoxic, and Non-aggregating red Fluorescent Protein for Long-Term Labeling of Fine Structures in Neurons - Ning, Lin; Geng, Yang; Lovett-Barron, Matthew; Niu, Xiaoman; Deng, Mengying; Wang, Liang; Ataie, Niloufar; Sens, Alex; Ng, Ho-Leung; Chen, Shoudeng; Deisseroth, Karl; Lin, Michael Z.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Red fluorescent proteins are useful as morphological markers in neurons, often complementing green fluorescent protein-based probes of neuronal activity. However, commonly used red fluorescent proteins show aggregation and toxicity in neurons or are dim. We report the engineering of a bright red fluorescent protein, Crimson, that enables long-term morphological labeling of neurons without aggregation or toxicity. Crimson is similar to mCherry and mKate2 in fluorescence spectra but is 100 and 28% greater in molecular brightness, respectively. We used a membrane-localized Crimson-CAAX to label thin neurites, dendritic spines and filopodia, enhancing detection of these small structures compared to cytosolic markers.